-9(3b+1)+(28b-2)=0

Simple and best practice solution for -9(3b+1)+(28b-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(3b+1)+(28b-2)=0 equation:


Simplifying
-9(3b + 1) + (28b + -2) = 0

Reorder the terms:
-9(1 + 3b) + (28b + -2) = 0
(1 * -9 + 3b * -9) + (28b + -2) = 0
(-9 + -27b) + (28b + -2) = 0

Reorder the terms:
-9 + -27b + (-2 + 28b) = 0

Remove parenthesis around (-2 + 28b)
-9 + -27b + -2 + 28b = 0

Reorder the terms:
-9 + -2 + -27b + 28b = 0

Combine like terms: -9 + -2 = -11
-11 + -27b + 28b = 0

Combine like terms: -27b + 28b = 1b
-11 + 1b = 0

Solving
-11 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1b = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 1b = 0 + 11
1b = 0 + 11

Combine like terms: 0 + 11 = 11
1b = 11

Divide each side by '1'.
b = 11

Simplifying
b = 11

See similar equations:

| 5x+9(x-17)=8(9+x)+6x | | 9(2.5)-10= | | 3(2.5)+5= | | 83-4x=23x+20 | | 7-7x=82-42x | | =20+3 | | h-6j+7h+10j= | | 3.2q-3.6-4.1q=1.9q-4.8 | | 4x+27=72-2x | | 6x+39=14x-25 | | 6x^2+49-45=0 | | 3[x-5]=9 | | 25x^2=-32 | | p+10p-5-3p= | | 136-2x=34x+24 | | 6y-2(y+4)=12 | | y+11=4x | | 10+15m-6m-2m= | | 123-6x=2x+11 | | 28x-X^2=192 | | x^2*x=y | | 5-3t=6t-22 | | 52-4x=23x+16 | | 4y+4=3x | | 8p-9=-2p+7 | | 0.3(x+20)-0.05(x-10)=14 | | 6x-29=31 | | (5r-1)(6r-3)= | | 7x+9+5x=-3x+14 | | t+38=7t+8 | | 2y=x-7 | | 3x-5=11x-29 |

Equations solver categories